Cover Picture: Recent fabrications and applications of cardiac patch in myocardial infarction treatment (View 2/2022). Issue 2 (21st March 2022) - Li, Mei; Wu, Hao; Yuan, Yuehui; Hu, Benhui; Gu, Ning
Abstract : In article number 20200153, Ning Gu, Benhui Hu and their co‐workers have shown that cardiac patches carrying cells, exosomes or gene can provide beneficial factors, mechanical support or electrical integration with the damaged heart in situ on the epicardium to help repair myocardial tissue and restore cardiac function.